2020
DOI: 10.1093/femsec/fiaa063
|View full text |Cite
|
Sign up to set email alerts
|

The roles of environmental variation and spatial distance in explaining diversity and biogeography of soil denitrifying communities in remote Tibetan wetlands

Abstract: The relative importance of local environments and dispersal limitation in shaping denitrifier community structure remains elusive. Here, we collected soils from 36 riverine, lacustrine and palustrine wetland sites on the remote Tibetan Plateau and characterized the soil denitrifier communities using high-throughput amplicon sequencing of the nirS and nirK genes. Results showed that the richness of nirS-type denitrifiers in riverine wetlands was significantly higher than that in lacustrine wetlands but not sign… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 68 publications
2
10
0
Order By: Relevance
“…Soil pH was an important factor controlling the diversity and composition of denitrifying communities in the environments ( Saleh-Lakha et al, 2009 ; Wise et al, 2019 ). However, there were no significant correlation between pH and denitrifier diversity, nirS-encoding or nirK-encoding denitrifier community structures in tundra soils ( Supplementary Table S3 ), similar to the results in Tibetan wetlands reported by Jiang et al (2020) . Other environmental factors, such as organic carbon and nitrite, had no significant contribution to nirS and nirK-encoding denirifiers community structures in this study, although they had been reported to have significant impact on denitrifying community compositions ( Mosier and Francis, 2010 ; Francis et al, 2013 ).…”
Section: Discussionsupporting
confidence: 83%
“…Soil pH was an important factor controlling the diversity and composition of denitrifying communities in the environments ( Saleh-Lakha et al, 2009 ; Wise et al, 2019 ). However, there were no significant correlation between pH and denitrifier diversity, nirS-encoding or nirK-encoding denitrifier community structures in tundra soils ( Supplementary Table S3 ), similar to the results in Tibetan wetlands reported by Jiang et al (2020) . Other environmental factors, such as organic carbon and nitrite, had no significant contribution to nirS and nirK-encoding denirifiers community structures in this study, although they had been reported to have significant impact on denitrifying community compositions ( Mosier and Francis, 2010 ; Francis et al, 2013 ).…”
Section: Discussionsupporting
confidence: 83%
“…In general, the majority of nirS sequences are mapped into unclassified groups or environmental clones (accounting for 38–70%), indicating that a large degree of nirS sequences are currently unavailable in the present genomic database. 52,53 Furthermore, a majority of the nirS sequences amplified with the primer set cd3aF/R3cd belonged to alpha-, beta- and gamma- proteobacteria . In soil systems, Bradyrhizobium was often found as the main nirS -type denitrifier.…”
Section: Identification Of Nirs-type Denitrifying Communitiesmentioning
confidence: 99%
“…Soil or sediment physicochemical properties including moisture, density, texture (i.e., the proportion of sand, silt, and clay) (hereinafter referred to as “sand”, “silt”, and “clay”), total carbon (TC), organic carbon (TOC), ammonium (NH 4 + ), nitrate (NO 3 – ), total nitrogen (TN), Ferrum (Fe), ferrous iron (Fe 2+ ), available iron (AFe), total phosphorus (P) and sulfate (SO 4 2− ) were determined in the laboratory, as described in detail in our previous work [ 31 , 32 ]. Other parameters, including pH and electric conductivity (EC), were measured using a YSI Professional Plus multi-parameter water quality meter (YSI Inc., Yellow Springs, Ohio, USA).…”
Section: Methodsmentioning
confidence: 99%
“…), nitrate (NO 3 -), total nitrogen (TN), Ferrum (Fe), ferrous iron (Fe 2+ ), available iron (AFe), total phosphorus (P) and sulfate (SO 4 2− ) were determined in the laboratory, as described in detail in our previous work [31,32]. Other parameters, including pH and electric conductivity (EC), were measured using a YSI Professional Plus multi-parameter water quality meter (YSI Inc., Yellow Springs, Ohio, USA).…”
mentioning
confidence: 99%